Pengembangan Sistem Informasi Penilaian Kinerja Guru berbasis Web (Studi Kasus: SMP Islam Sabilurrosyad) - Intan Wahyuningtias; Ismiarta Aknuranda; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
SMP Islam Sabilurrosyad Malang is an educational institution that has human resources, especially teachers. Teachers have an important role in schools with the main task of educating, teaching, guiding, and directing students. In this role, to achieve optimal learning, teachers must be able to improve their performance and professionalism. Improving teacher performance can be improved by making efforts in the form of teacher performance appraisal (PKG). SMP Islam Sabilurrosyad has never conducted teacher performance appraisals before, so it is necessary to seek in-depth information and needs regarding the flow and components of teacher performance appraisals. On the other hand, teacher performance appraisal is needed to improve teacher quality and as a consideration for school principals to determine teacher salaries. This study aims to obtain the flow of teacher performance appraisal and be implemented in a web-based teacher performance appraisal information system. We built a teacher performance appraisal information system using an iterative approach and implemented using the Laravel framework and the Stisla framework. The results of the implementation of the information system are evaluated by conducting validation testing and browser compatibility testing. The validation test results produce valid results in every test case, while the browser compatibility test results show good results and there are no problems in the eight versions of the browser.